Practices of Constructing Regional Identity in the Media Discourse of Tatarstan - O. V. Ilyina; E. V. Kablukov (Научный диалог, 2020)
The authors consider identity as a conditional discursive construct, the result of subjects of discourse identifications and offer their own methodology for its analysis. It is shown that regional identity can be represented in the form of a model based on spatial and temporal identifications that specify the coordinate system of reality in which there are residents of the region in question. The concept of space-time is complemented by a set of diverse thematic identifications, including economic, political, cultural, ethnic, religious, linguistic, etc. For the first time in the framework of the socio-constructionist paradigm, a discursive model of the regional identity of the inhabitants of Tatarstan is constructed in the article. The empirical material of the study is the corpus of texts of Tatarstan media for 2017-2019. It is shown that the spatial identification of Tatarstan people includes the practice of selecting, nominating and describing significant geographical objects, the practice of constructing relations of Tatarstan with other geographical objects. Particular attention is paid to the practice of constructing the capital status of a regional center, as well as the relationship of spatial and political identifications. Analyzing the practices of ethnic, religious, linguistic and cultural identification, the authors come to the conclusion that the identity of the Tatarstan people is ethnocentric: despite the declared multinationality and multi-confessionality of the region, Tatars as an ethnic group, Tatar language, Tatar culture and Islam as a traditional religion of the Tatars are of particular importance.